Kesetaraan Gender: Perempuan Dalam Perspektif Ajaran Gereja Katolik Menurut Gaudium Et Spes - Fransesco Agnes Ranubaya; Yohanes Endi (Jayapangus Press, 2023)
The Catholic Church has always provided space to fight for justice and gender equality to fulfill God's mission in the world. Women's lives have changed dramatically over the past quarter century. Progress on gender equality remains limited. The still strong patriarchal culture prolongs the suffering of the helpless and complicates the struggle and change toward justice and gender equality. Discrimination against women is a common problem in almost all occupations, even in most parts of the world. It can be understood that gender is a distinction that is neither biological nor divine nature. The purpose of this study is to raise the theme of gender equality which is discussed based on Church documents, namely Gaudium Et Spes art. 9 and art. 29. This research uses a type of library research, which has the aim of tracing and analyzing data or information about the essence of Gaudium Et Spes Article 9 and Article 29 documents concerning Gender Equality. The contribution of Gaudium Et Spes Art. 9 and Art. 29 is that the similarities between men and women are through the institution of goodwill in the sense that both men and women participate in what the church stands for, which is the struggle to shape human life more humanely. The Catholic Church also stressed that this will take a long time, considering that the fight for gender equality is not easy, especially in a world that is heavily influenced by patriarchy. In addition, this research is useful to open horizons regarding gender equality and everyone, both men and women, realize the differences that exist as God's goodwill. Through this document, the Church strives to think about how gender issues are taken seriously to avoid injustices in public life.